The Act of Memory In Wordsworth's "The Prelude" - Ahmad H. Mohammed; Rai'a A. Abdul Aziz (PROSPECTIVE RESEARCHES, 2023)
This study aims at shedding light on the role of memory in poetry. It traces back this role in the first survival literary works. It concentrates on the act of memory as it appears in Wordsworth's "The Prelude" which can easily be touched in the poet's treatment of certain spots of time. These spots stop the poet and help him decorate his faculty in some water images which scatter in the poem. These roles are scientifically studied and interpreted according to some psychological theories.